Effects of sulphate salts on concrete with untreated coal fly ash (CFA) as partial cement replacement. Issue 2 (9th May 2016) - Coopamootoo, Kumaran; Rughooputh, Reshma
Abstract : Purpose: – The cementitious/chemical properties of the untreated CFA are dependent on the coal composition and previous burning conditions. The purpose of this paper is to investigate whether untreated CFA can efficiently reduce cement replacement and does not require further combustion treatment to be a viable cement replacement. Design/methodology/approach: – Two types of mixes: Type I concrete and PCFA (Type I and 30 per cent untreated CFA) concrete were batched and subjected to compressive strength tests and cyclic exposures of 5 per cent sodium sulphate (Na2 SO4 ) and 5 per cent magnesium sulphate (MgSO4 ), respectively. Findings: – PCFA mix was 41.1 and 35.21 per cent lower in strength compared to Type I at 28 and 56 days correspondingly. Continuous-sulphate-exposure resulted in slow but continued strength development for both mixes. However, the strengths of PCFA cubes exposed to cyclic sulphate and sulphate/magnesium salts continued to increase at a lower rate from their corresponding 28-day strength (rate of 18.7 per cent and strength 27.30 MPa in Na2 SO4 and rate of 10.0 per cent and strength 25.30 MPa in MgSO4 ) while Type I specimens subjected to the same exposure conditions experienced drastic reductions in strength (rate of −15.0 per cent and strength 33.21 MPa in Na2 SO4 and rate of −23.4 per cent and strength 29.94 MPa in MgSO4 ). Research limitations/implications: – Results justify the need for additional tests essentially: at different percentage replacement of untreated CFA, fineness of materials, chloride environment and longer exposures, to address the cementitious properties of untreated CFA as cement replacement. Originality/value: – Treatment methods for fly ashes require undoubtedly additional resources, energy input and cost. This paper paves the way to define whether untreated CFA can be used as cement replacement in concrete.